A review of the mud-dauber wasps of genus Sceliphron Klug (Hymenoptera: Sphecidae) from India - Anagha, S.; Kumar, P. Girish; Binoy, C.; Mazumdar, P. C.; Sureshan, P. M. (Zootaxa, 2021)
The mud-dauber wasp genus Sceliphron Klug (Hymenoptera: Sphecidae) is reviewed, with six species and six subspecies reported from various parts of India. The Palaerctic species, S. destillatorium (Illiger), is recorded for the first time from the Indian subcontinent. The subspecies S. madraspatanum formosanum van der Vecht is also recorded for first time from the Indian subcontinent. The distribution records of species and subspecies within various states of India are augmented. A modified key to the species of Sceliphron occurring in India is provided. Intraspecific variation within nominal species is discussed.